2016
DOI: 10.1149/2.0631607jes
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Re-Ni Films after the Initial Stages of Electrodeposition

Abstract: Re-Ni layers produced in the early stages of electrodeposition from citrate electrolytes were studied by high-resolution X-ray photoelectron spectroscopy (HR-XPS) and time-of-flight secondary-ion mass spectrometry (TOF-SIMS). The deposition time was varied in the range of 2 to 300 seconds. The compositional heterogeneity of the thin Re-Ni alloys and the variations of their composition with deposition time, both in the bulk and on the surface, were shown. The results obtained are indicative of the occurrence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous work in our laboratory has found that the addition of one of the iron-group metals (Ni, Co, or Fe) to the solution bath leads to high Faradaic efficiency (FE) and high Re-content in the deposits. This catalytic effect of iron-group metals on Re electrodeposition, as well as the mechanism of codeposition has been investigated in detail in our lab in recent years [11][12][13][14][19][20][21]. The Re-Ni alloy system is of particular interest because of the extensive mutual solubility of Re and Ni and the absence of intermetallic compounds in the Re-Ni peritectic phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in our laboratory has found that the addition of one of the iron-group metals (Ni, Co, or Fe) to the solution bath leads to high Faradaic efficiency (FE) and high Re-content in the deposits. This catalytic effect of iron-group metals on Re electrodeposition, as well as the mechanism of codeposition has been investigated in detail in our lab in recent years [11][12][13][14][19][20][21]. The Re-Ni alloy system is of particular interest because of the extensive mutual solubility of Re and Ni and the absence of intermetallic compounds in the Re-Ni peritectic phase diagram.…”
Section: Introductionmentioning
confidence: 99%